ENVIRONMENTAL INFLUENCE ON THE BIOHOPANOID COMPOSITION OF RECENT SEDIMENTS - Farrimond P.; Head I.M.; Innes H.E. (My University, 2000)
Bacteriohopanepolyols are the biological precursors of extended hopane biomarkers which are ubiquitous in the geosphere. The abundance and composition of these biohopanoids were determined for modern sediments from eight depositional environments by GC-MS analysis of hopanols derived from a side-chain cleavage reaction (periodic acid and sodium borohydride) of the bacteriohopanepolyols. We report quantitative data for bacteriohopanetetrol (BHT), composite tetrafunctionalised biohopanoids, pentafunctionalised biohopanoids and hexafunctionalised biohopanoids. BHT was found in concentrations higher than previously reported (up to ca. 1500 μg/g TOC), but comprised only a relatively small proportion (0-26%) of the total biohopanoids in all except one sample. Composite tetrafunctionalised biohopanoids were the dominant group of bacteriohopanepolyols in all other sediments, and are likely to be a major source of the geologically occurring extended hopanes. Hexafunctionalised biohopanoids were most abundant in lake sediments, particularly two small highly productive stratified lakes (where they comprised 20-40% of total biohopanoids). This feature is interpreted to be due to greater contribution to the organic matter of these sediments from Type I methanotrophic bacteria (which produce dominantly hexafunctionalised biohopanoids), consistent with the environmental settings. In the marine environments where sulphate reduction is dominant, hexafunctionalised biohopanoids are relatively minor constituents (2-6% of total biohopanoids). These data comprise the first clear demonstration that bacteriohopanepolyols vary in composition between depositional environments, and have the potential to preserve specific bacterial source information in sedimentary organic matter.